1995
DOI: 10.1046/j.1537-2995.1995.351096026362.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of the K:6,‐7 [Js(a+b−)] phenotype in the Kell blood group system

Abstract: The base substitutions T-to-C at nt 1910 and A-to-G at nt 2019 are unique to KEL6. The predicted Leu-->Pro change may disrupt the alpha-helical structure and thus form the epitope for KEL6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 14 publications
1
26
0
2
Order By: Relevance
“…2). This result is in accordance with previously published studies that have shown that K1 antigenic sites were found in equivalent quantities to K2 sites on heterozygous red cells (50), suggesting that, despite its modified sequence and as demonstrated here, polysaccharide content, K1 still attains a conformation validated within the ER compartment, a conformation that, at the cell surface, possesses superior antigenicity than that of Kell K2 (29). Thus it appears that there may be many "correct" conformations to one protein or that subtle conformational changes cannot be distinguished within the ER, even though both antigens may display different retention times within this compartment (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…2). This result is in accordance with previously published studies that have shown that K1 antigenic sites were found in equivalent quantities to K2 sites on heterozygous red cells (50), suggesting that, despite its modified sequence and as demonstrated here, polysaccharide content, K1 still attains a conformation validated within the ER compartment, a conformation that, at the cell surface, possesses superior antigenicity than that of Kell K2 (29). Thus it appears that there may be many "correct" conformations to one protein or that subtle conformational changes cannot be distinguished within the ER, even though both antigens may display different retention times within this compartment (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…Among the identified point mutations of the Kell system so far, one may affect such a process, that of Kell K1, which is defined by a C to T base substitution in exon 6 leading to the replacement of a threonine by a methionine residue (T193M) within a putative N-glycosylation consensus sequence Asn-X-Thr/Ser. This mutation could alter the polysaccharide content of Kell and lead to a change in protein conformation and/or trafficking into the cellular machinery (29), which could in turn affect its function.…”
mentioning
confidence: 99%
“…41 Because KEL6 has an incidence of 20% in persons of African heritage and occurs only in about 0.01% in whites, it is thought that this unequal distribution may reflect a selection pressure that influences the functional properties of Kell. However, the model does not indicate that the Leu597Pro mutation is in close spatial relation with the enzymeactive site.…”
Section: Kell Blood Group Antigens Are Clustered On the Nonconserved mentioning
confidence: 99%
“…For example, KEL1 is present in 9% of Caucasians and in 2% of persons of African heritage, whereas KEL6 is present in 20% of persons of African heritage and in less than 1% of Caucasians. KEL1 is due to a 698C3 T mutation that results in a Thr 193 3 Met substitution at an N-glycosylation consensus sequence (3). KEL6 is due to a 1910T3 C mutation that results in a Leu 597 3 Pro substitution, which is located between two closely placed non-conserved cysteine residues (596CPAC599), and the antigen is more sensitive to reducing agents (4).…”
mentioning
confidence: 99%